Reply to letter having reference number BUCG-ABC JV/BRACU/24/18 dated 28th April 2018 - Brac University (Brac University, 2023)
This record consists of general correspondence regarding reply to letter having reference number BUCG-ABC JV/BRACU/24/18 dated 28th April 2018 addressing the issue of substantiation of claims due to the defective diaphragm wall of BRAC University new campus project.